Shifting Paradigms: The Impact of Streaming on Diversity in Academic Library Film Collections - Deck, Trevor; Clarkson, Amelia; Mason, James (Canadian Journal of Academic Librarianship / Revue canadienne de bibliothéconomie universitaire)

(untitled) (Canadian Association of Professional Academic Librarians / Association Canadienne des Bibliothécaires en Enseignement Supérieur, 2024)
Investigations into format shifts from physical to digital access in libraries often centre print materials. Similarly, recent calls to action for an increasing focus on acquisition of materials that support equity, diversity, and inclusion (EDI) efforts within postsecondary institutions often centre print resources. For academic libraries, media like film have unique access and acquisition models that do not correspond to print and pose unique challenges extending back to the Hollywood studios that create and distribute films. This paper explores the dual shifts in academic libraries toward collecting fewer physical films and collecting more content to support EDI mandates, and asks: first, whether the shift away from collecting physical media may also be a shift away from including diverse perspectives in film collections; and second, if we have the data to draw a measurable and demonstrable conclusion. A comprehensive literature review traces efforts to assess markers of diversity in large library collections and/or film collections over the past two decades and helps establish a methodology that combines analyzing data from the library catalogue and Wikidata. Findings revealed that the completeness and consistency of the data over time makes drawing strong conclusions difficult and demonstrated the challenges of this approach in addressing EDI analysis, even when augmenting catalogue metadata with Wikidata. Curation and choice are perhaps more important in building a diverse film collection than questions of format alone, despite the challenges in assessing and collecting film which is and has always been a format in rapid and continual flux.